Navigating Ottawa Resources To improve Health: a virtual student-clinic pilot to strengthen social medicine education - Seung Heyck Lee; Aravinth Jebanesan; Katelyn Wang; Nicole Wisener; Emily Liang; Makenna Timm; Claire E Kendall; Susan Bennett (Canadian Medical Education Journal)
Implication Statement